Effectiveness of Project-Based Learning in Textile Dyeing Course to Improve Work Readiness as Entrepreneurs in the Digital Era - Sri Zulfia Novrita; Nizwardi Jalinus; Ridwan; Rijal Abdullah; Weni Nelmira; Adriani (Postgraduate, University of Mataram, 2025)
Student work readiness in facing the world of digital entrepreneurship is still an obstacle that requires a more effective learning approach. This study aims to examine the effectiveness of project-based learning model on students' work readiness in digital era entrepreneurship. By using pre-test and post-test design, 40 students were prepared to be tested at the beginning and at the end who were taught using a project-based learning model. Students participated in the learning process for one semester with real-world projects relevant to the digital fashion industry. The t-test results indicate a significant difference between pretest and posttest scores (t-calculated = 38.561 > t-table = 1.990; sig. < 0.05), indicating a significant improvement in digital work readiness. This improvement includes technical skills, creativity, digital literacy, collaboration, and business management skills based on technology. Additionally, project-based learning was proven to enhance students' motivation and engagement in the learning process. These findings reinforce the effectiveness of PjBL as an approach responsive to the demands of Industry 4.0. This study concludes that the project-based learning model is effective in preparing competent graduates in digital entrepreneurship and can be adopted as an adaptive and applicable vocational learning strategy in the era of digital transformation.